PENELITIAN KUANTITATIF STATISTIK PERKEMBANGAN TAHFIDZ MAHASISWA PASCASARJANA UMT TAHUN 2023 - rukmono (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2023)
The aim of this research is to tell other the progress tahfidz program graduate studentUniversitas Muhammadiyah Tangerang (UMT). This work is a quantitative research, whichis processing data into statistics and make analyze process of tahfidz program especially forgraduate student UMT. Background of this research is because we have not yet any researchfocused develop of tahfidz program for graduate student at UMT. Because of that, we cannot evaluate the progress of this program and also we are facing a problem to fixed thisprogram if there are any something need to fixed. Why we use data of graduate studentUMT? The answer is because they are important person who chosen UMT as a place tocontinue their study. Usefulness of this research is Al-Islam Kemuhammadiyahan (AIK) asa board who responsibilities this program finally has a guide to evaluate develop thisprogram. Base this research, AIK can fixed problem this program if there are any somethingneeded to fix for better forward. In this research we use statistics quantitative to processdata. We are transform data into graphics so that we can see easily the progress of graduatestudent tahfidz program. Not only that of our work, we also did count percentage of theirprogress every single week form week 84-85, 85-86, 86-87, until week 87-88. As a theory,the result of this research should be the percentage spread from 0% until 100%. Percentage0% means that there is no one that in a week used by graduate student to do tahfidz, insteadof that, percentage 100 % giving mean that students use fully 7 days in a week to do tahfidz.Keywords: Quantitative, Statistics, Tahfidz, Graduate, Student